2007
DOI: 10.1371/journal.pbio.0050158
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Oligomerization Targets Plasma Membrane Proteins and HIV Gag to Exosomes

Abstract: Exosomes are secreted organelles that have the same topology as the cell and bud outward (outward is defined as away from the cytoplasm) from endosome membranes or endosome-like domains of plasma membrane. Here we describe an exosomal protein-sorting pathway in Jurkat T cells that selects cargo proteins on the basis of both higher-order oligomerization (the oligomerization of oligomers) and plasma membrane association, acts on proteins seemingly without regard to their function, sequence, topology, or mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
339
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(357 citation statements)
references
References 64 publications
16
339
2
Order By: Relevance
“…The WD40 domain controls this behavior, likely by mediating the formation of higher-order oligomers. It has been reported that high-order oligomerization and membrane-binding motifs artificially target cytosolic proteins to membrane patches, which accumulate at the lagging edge in polarized cells (48)(49)(50)(51)(52). Oligomerizing membrane microdomain components also enrich at the rear of polarized neutrophils or T cells (53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…The WD40 domain controls this behavior, likely by mediating the formation of higher-order oligomers. It has been reported that high-order oligomerization and membrane-binding motifs artificially target cytosolic proteins to membrane patches, which accumulate at the lagging edge in polarized cells (48)(49)(50)(51)(52). Oligomerizing membrane microdomain components also enrich at the rear of polarized neutrophils or T cells (53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…This final step is thought to be mediated by ESCRT-III, possibly in conjuction with the ATPase VPS4 (33,49). In the conception of these experiments, we had anticipated that inefficient release of Gag puncta into the GUV interior might be seen even in the absence of ESCRTs, because high levels of Gag overexpression have been shown to drive budding (50). If ESCRT-III assembly were sufficient for scission, as seen for the yeast proteins, we would have expected to see a large increase in VLP release upon completion of ESCRTassembly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, plasma membrane anchors induce vesicle budding directly from the plasma membrane of highly oligomeric proteins, such as the HIV Gag protein and the yeast cytoplasmic protein Tya [123,124]. An evaluation of different membrane anchors for Tya demonstrated that myristoylation was the most effective enhancer of the formation of shedding vesicles, whereas other types such as, phosphatidylinositol-(4,5)-bisphosphate and phosphatidylinositol-(3,4,5)-trisphosphate-binding domains, prenylation/palmitoylation tag or the type-1 plasma membrane protein CD43 did not cause this effect [124].…”
Section: Other Ptms In Evsmentioning
confidence: 99%